BUSINESS PROCESS MODEL AND NOTATION (BPMN) DONAT MADU CIHANJUANG - Deni Heryanto; Vemy Suci Asih (Masoem University, 2018)
This paper discusses the business process modeling at Donat Madu Cihanjuang, the purpose of this research is to model the business process using BPMN to improve in terms of service for consumers, starting from literature study and data collection through interview. Further modeling and simulation of current business processes using BPMN, problem analysis, modeling and simulation of proposed business processes and comparison of results. The method used is Business Process Improvement (BPI) approach. The results obtained are proposed modeling new business processes in improving services to customers (consumers).